Detection response of the active components of the SciBar Cosmic Ray Telescope at Sierra Negra - F. Monterde-Andrade; L. X. González; J. F. Valdés-Galicia; O. G. Morales-Olivares; M. A. Sergeeva; J. Newton-Bosch; E. Ortiz; A. Hurtado; R. Taylor; Y. Matsubara; T. Sako; Y. Itow; et al. (European Physical Journal C: Particles and Fields)
Abstract The Scibar Cosmic-Ray Telescope (SciCRT) is the most promising detector of the Sierra Negra Cosmic Rays Observatory (SN-CRO). At this location, being a target and a tracker of secondary cosmic rays, the SciCRT offers a high probability of observing solar energetic particles and lower energy galactic cosmic rays (LEGCR); also, it allows the identification of incoming particles by measuring their energy deposition. In this work we present a Geant4-based simulation of the energy deposited by neutrons, $$γ $$ γ -rays, protons, electrons and muons in the optimally running SciCRT components. We also calculated the detection efficiency of the SciCRT at its current state. Our simulation results provide new information about the SciCRT detection response that may be used as a basis to estimate and analyze the energy spectra of primary particles.